Environmental Management for Poultry Farm - Sri Rachmawati (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Attention has to be given to farming management, housing and waste handling in order to achieve an efficient farming and also to maintain a good environmental quality. A literature review was conducted to find out kinds of waste discharged from poultry farm, the effect of waste to environment and health and its handling and monitoring methods. Environmental problem of poultry farm comes from manure that causes bad odor. The source of odor is from the formation of ammonia and hydrogen sulfide gases, nitrate, and nitrite during decomposition process of manure. Air polluted by those gases can cause disturbance to chicken health and people who live near the farm. Ammonia can inhibit the growth of chicken and cause eyes irritation and respiratory problem to human being. Methods of odor handling using zeolite, lime, and microorganism have been attempted. Those materials, which are added into manure, can reduce the formation of ammonia and hydrogen sulfide gases. The manure can also be used as an organic fertilizer, and the farmer obtains good benefit from it, because it has high nitrogen content. To maintain a good environmental quality, especially from manure odor, continuous environmental monitoring has to be done that involving people who live around the farm. Their perception about manure odor has to be taken into consideration and they are also asked to report any problems caused by the pollution of manure odor.   Key words: Handling, manure, monitoring